Sind Haushalte mit Wohneigentum sparsamer als Mieterhaushalte? - Ruth Grunert (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
– In this paper examines the data of the income and consumption survey of 1998 with regard to savings and wealth. Households owning their property (owner households) and households renting the property (tenant households) are analysed seperatly and then compared. For further insight these two groups are also devided into East and West German households. In 1998, almost half of the West German and almost a quarter of the East German private households owned property they occupied themselves. The average owner household saves a monthly amount three times as large as the tenant household. The decisive economizing motive for the owner households is servicing its mortgages and loans. However, at the same time, there is the necessity to form reserves for the property maintainance as well as the renovation. In comparison to tenant households, owner households which no longer have to service mortgages or loans, have a higher average rate of saving. The estimate of the saving by means of regression analysis confirms the significant positive influence of the 'owner' status on savings. However, in every estimate the houshold's income proves to be the main influence on savings activity.
urn:nbn:de:gbv:3:2-20362
Keywords: 330; Sparen; Vermögensbildung; Wohneigentum; Privater Haushalt; Deutschland